Pengaruh Beberapa Jenis Pupuk Hayati terhadap Pertumbuhan Dua Klon Tanaman Teh (Camellia sinensis (L) O. Kuntze) Belum Menghasilkan - Ade Wachjar; , Supijatno; Dina Rubiana (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The experiment was carried out to study the effect of biofertilizer on the growth of two clones of young tea. This experiment was conducted at Cikabayan Experiment Station, Faculty of Agricuture, IPB, Bogor, from July to November 2000. This experiment was arranged in Split Plot Design with three replications. The main factor was clone types consisted of two clones i.e.: RB 3 and Gambung 5, whereas the sub factor was biofertilizer consisted of five kinds i.e. : EMAS + 50 % inorganic fertilizer recommended dosage (i.f.r.d.), EM4 + 50 % i.f.r.d., OST + 50 % i.f.r.d., Soils Plus + 50 % i.f.r.d. and 100 % i.f.r.d. The results showed that the EMAS + 50 % i.f.r.d. and EM4 + 50 % i.f.r.d. treatments significantly increased plant height, stem diameter, leaf number, and bud length. The application of 6.25 g EMAS per plant (equivalent with 83.125 kg/ha) + 50 % i.f.r.d. and 10 ml EM4 (equivalent with 6.65 l/ha) + 50 % i.f.r.d. could reduce application of inorganic fertilizer dosage until 50 % and resulted in the growth of the plant which was better than that of inorganic fertilizer. In general, growth of the RB 3 clone was better than Gambung 5 clone. Key words : Biofertilizer, clones, vegetative growth, tea